What Inez Knows: A Qualitative, Longitudinal Case Study of One Woman's Journey Through the Maze of Living with Hiv and a Serious Mental Illness - (:unkn) unknown (My University, 2014)
WHAT INEZ KNOWS: A QUALITATIVE, LONGITUDINAL CASE STUDY OF ONE WOMAN'S JOURNEY THROUGH THE MAZE OF LIVING WITH HIV AND A SERIOUS MENTAL ILLNESS by Linda Austin The University of Wisconsin-Milwaukee, 2014 Under the Supervision of Professor Patricia E. Stevens Although more than thirty years have passed since AIDS was first diagnosed in the U. S., the HIV/AIDS epidemic continues and the prevalence and incidence statistics remain alarming. Twenty-five percent of the people living with HIV in the United States are women, but only half of these women are in care and even fewer women (42%) have viral suppression. Women of color continue to carry a disproportional disease burden with African American women comprising 64% of newly reported HIV cases in women in 2010. HIV prevalence among adults with a serious mental illness range from 3-23% compared to the general population prevalence (.4-.6%). Based on these facts, there is continuing need to explore the dual experience of HIV infection and serious mental illness in women. Research that focuses on the women and seeks to understand the particulars of their lives may offer greater insight into how the health care community can improve their outcomes. Inez (pseudonym) is an African American woman dually diagnosed with HIV infection and a severe and persistent mental illness. She was one of 55 participants in the qualitative study, In-Depth Longitudinal Study of HIV-Infected Women (National Institutes of Health, Grant #R01NR004840, Principal Investigator, Patricia E. Stevens, PhD, RN, FAAN). In this secondary analysis, her narrative data were segregated from the original study, analyzed, and used to develop an in-depth, longitudinal case study. The purpose of this study was to uncover Inez's perceptions of what it means to live with HIV and a serious mental illness. Through this single case study replete with experiential detail from two years of interviews, we are given an extraordinary view into how one individual lives with HIV and a serious mental illness, what she needs from the health care community to successfully manage her illnesses, and how mutually respectful relationships built over time are key to overcoming internalized and enacted stigma. Inez's story confirms the importance of therapeutic, respectful communication, and stability of care provided in an environment of cultural safety where the perspectives of health care consumers are prioritized. In addition to these practice implications, this research-based case study could be used in problem-based classroom learning environments to inspire students to consider ways to improve the experiences of women who are similar to Inez.
Keywords: Case Study; HIV; Mental Illness; Qualitative; Women